Use of video image analyses to identify carcass characteristics and sensory quality of beef products generated from mature cow carcasses - Woerner, Dale R., author; Belk, Keith E., advisor; Tatum, J. Daryl, advisor (Colorado State University. Libraries, 2009)
A single study (sponsored by the beef check-off) was conducted to investigate the ability of video image analysis technology to identify carcass characteristics and sensory attributes of products generated from mature cow carcasses. Market cows representing three pre-harvest management strategies were used to evaluate the ability of video image analysis (VIA) to identify the impacts of pre-harvest management (MGMT) on carcass muscle and beef sensory characteristics. Cow MGMT groups were as follows: (1) Non-fed cows (n = 104) (NON-FED; beef-type cows entering the slaughter facility as culls from sale barns and/or ranching operations); (2) Fed cows (n = 108) (FED; beef-type cows entering the slaughter facility from a finishing yard having received a corn-based, high energy diet for a 95 d ± 1 d period); (3) Dairy cows (n = 113) (DAIRY; cows entering the slaughter facility directly from dairies as culls). FED market cows were fatter, heavier, and more muscular than either NON-FED or DAIRY cows. DAIRY cows were slightly fatter (in the carcass), heavier, and less muscular (alive, muscle score) than were NON-FED beef cows. FED beef cows had the most desirable lean color scores, the most tender LM steaks, and had whiter colored fat than NON-FED beef cows. DAIRY cows were the most youthful (lowest SKELMAT and dentition scores) at the time of harvest and produced carcasses that had similar marbling and fat color scores to those of FED beef cow carcasses. NON-FED beef cows produced the lowest marbling scores, the toughest LM steaks, and the most yellow colored fat. Correspondingly, fat from NON-FED beef cows had the highest concentrations of vitamin A and 3-carotene in the fat. NON-FED cows had the greatest probability of producing beef with undesirable flavor attributes but no meaningful differences were found among MGMT groups in fatty acid composition. Cow LM representing all MGMT groups responded to postmortem muscle-aging (P < 0.001) whereas the PM did not (P = 0.075). A MGMT x postmortem muscle aging time interaction existed for the INFRA (P < 0.042). A significant interaction of MGMT x evaluation method (USDA grader vs. VIA instrument) existed for marbling score, LMA, and 12th rib fat thickness. Compared to USDA grader determined values, VIA instrument scores were higher for marbling score and lower for LMA. A prediction model developed from VIA instrument outputs demonstrated the ability to characterize the MGMT of cow with less than 13% error. The findings of this research warrant the continued development VIA instruments to identify cow carcass characteristics and sensory quality.
Keywords: beef products; carcass characteristics; cow carcasses; sensory quality; animal sciences